2016
DOI: 10.1111/ssqu.12291
|View full text |Cite
|
Sign up to set email alerts
|

Income Poverty and Multiple Deprivations in a High‐Income Country: The Case of the United States*

Abstract: Objectives The objective of this study is to develop a measure of multiple deprivations for the United States that is similar to those used on the international stage as multidimensional poverty. The latter is understood broadly as a deprivation of well‐being across multiple dimensions rather than purely as a lack of income or other financial resources. Methods Using Current Population Survey and American Community Survey data, this study develops a measure of the joint distribution of multiple deprivations in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 28 publications
0
14
1
Order By: Relevance
“…Typically, indicators of multidimensional poverty in the United States include health insurance, high-school education, housing costs, and disabilities. Mitra and Brucker [ 31 ] found that in 2012 a greater proportion of Hispanics were deprived in three or more indicators of poverty. Dhongde and Haveman [ 4 ] found that between 2008 and 2013, about 40% of Hispanics were multidimensional poor compared with 14% in the general population.…”
Section: Deprivation By Race and Ethnicitymentioning
confidence: 99%
“…Typically, indicators of multidimensional poverty in the United States include health insurance, high-school education, housing costs, and disabilities. Mitra and Brucker [ 31 ] found that in 2012 a greater proportion of Hispanics were deprived in three or more indicators of poverty. Dhongde and Haveman [ 4 ] found that between 2008 and 2013, about 40% of Hispanics were multidimensional poor compared with 14% in the general population.…”
Section: Deprivation By Race and Ethnicitymentioning
confidence: 99%
“…al. ( 2019 ) 4.6% Education High school education Not having received at least a high school diploma Dhongde and Haveman ( 2017 ) Glassman ( 2019 , 2021 ) Mitra and Brucker ( 2016 , 2019 ) Dhongde et. al.…”
Section: Introductionmentioning
confidence: 99%
“…al. ( 2019 ) Dhongde and Dong ( 2022 ) 10.2% Economic Security Health insurance Lack of any type of health insurance; public or private Dhongde and Haveman ( 2017 ) Glassman ( 2019 , 2021 ) Mitra and Brucker ( 2016 , 2019 ) Dhongde et. al.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations